Oral glucose tolerance test: Ηow to maximize its diagnostic value in children and adolescents : Reproducibility and accuracy of oral glucose tolerance test - De Sanctis, Vincenzo; Soliman, Ashraf; Daar, Shahina; Tzoulis, Ploutarchos; Di Maio, Salvatore; Kattamis, Christos (Acta Biomedica Atenei Parmensis, 2022)
Background: Recently, the validity of the oral glucose tolerance test (OGTT) as a gold-standard test for the diagnosis of glucose dysregulation (GD) has been questioned due to the pre-analytical, analytical, and post-analytical variables which can potentially affect its reproducibility and accuracy. Aims: In this short update, the many variables that affect the reproducibility and accuracy of the OGTT are described and discussed aiming to enhance its diagnostic value in clinical practice. Search strategy: A systematic search was implemented in June 2022, using Scopus, PubMed, Embase and Google Scholar focusing on OGTT relevant papers published in the last 10 years. Moreover, the reference lists of these articles were checked for additional pertinent studies. The research and selection of articles was also supported by the long-term authors’ experience in the use of OGTT for the diagnosis of GD in children and adolescents. Conclusion: The complexity of diagnosing GD presupposes that clinicians have specific knowledge and experience to perform rigorous assessment of glucose metabolism. It is worth mentioning that during OGTT, subjects with glucose levels close to the cut-off values proposed by WHO (World Health Organization)/ADA (American Diabetes Association) require careful evaluation in order to avoid misclassification and unnecessary interventions. For this reason, ADA recommends a second test to confirm the diagnosis of diabetes.